Evaluation of salivary gland ultrasonography in primary Sjogren's syndrome: does it reflect clinical activity and outcome of the disease? - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2019)
Objective. To evaluate associations between salivary gland ultrasonography (SGUS) and clinical characteristics, disease activity and outcome in patients with primary Sjogren's syndrome (pSS). Methods. The parotid and submandibular salivary glands were examined by ultrasonography using two different scoring systems proposed by Hocevar et al. and Milic et al. on 85 pSS patients. Patients with inhomogeneity/hypoechoic areas with scores >= 2 in parotid and submandibular glands were classified as severe parotid or severe submandibular involvements, respectively. Disease activity and patient-reported severity were evaluated using the European League Against Rheumatism Sjogren's Disease Activity Index (ESSDAI) and the European League Against Rheumatism Sjogren's Patient Reported Index (ESSPRI). Salivary gland functional capacity was investigated by unstimulated whole saliva flow rate (U-WSFR). Results. Of the activity scores, ESSPRI dryness component was higher in pSS patients who had scores above the cut-off values for Hocevar (6.1 +/- 2.3 vs. 4.9 +/- 2.6, p=0.02 6). The patients with any type of systemic involvement more frequently showed higher SGUS scores, according to both Hocevar (72.4 vs. 44.6%, p=0.01 3) and Milic (75.9 vs. 51.8%, p=0.026). These patients also showed a higher percentage of severe parotid/submandibular changes on US imaging (65.5 vs. 33.9%, p=0.005 and 75.9 vs. 51.8%, p=0.02 6 respectively). Higher SGUS scores according to cut-off values of both scoring systems and severe parotid/submandibular involvements were associated with both anti-Ro or double anti-Ro/La autoantibodies and inversely associated with U-WSFR. Conclusion. SGUS may be a useful imaging modality for the selection of patients with more severe disease status or who may require a tight follow-up schedule.
Keywords: salivary gland ultrasonography; primary Sjogren's syndrome; disease activity; CLASSIFICATION CRITERIA; DIAGNOSTIC-VALUE; SIALOGRAPHY; ULTRASOUND; SCORE; RITUXIMAB; CONSENSUS; TOOL